2003
DOI: 10.1080/08039480310000194
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of needs and quality of life in persons with schizophrenia living in the community. A Nordic multi-center study

Abstract: The relationship between needs for care and support and subjective quality of life was investigated in a cross-sectional multi-center study including 418 individuals with schizophrenia from 10 centers in Nordic countries. Needs in 22 domains were investigated by interviews with key workers and their patients using the Camberwell Assessment of Need scale, and quality of life by the Lancashire Quality of Life Profile. The results showed that key workers rated slightly more needs than patients. To have more unmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
48
0
6

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 27 publications
(33 reference statements)
9
48
0
6
Order By: Relevance
“…Cross-sectional studies [3,9,10,32,35,39] have confirmed the interrelation between unmet needs and quality of life including patients with high, medium, and low levels of functioning [3]. For met needs, the interrelation with quality of life was less consistent.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Cross-sectional studies [3,9,10,32,35,39] have confirmed the interrelation between unmet needs and quality of life including patients with high, medium, and low levels of functioning [3]. For met needs, the interrelation with quality of life was less consistent.…”
mentioning
confidence: 82%
“…For met needs, the interrelation with quality of life was less consistent. Some studies found a negative association (the more met needs the lower the quality of life) [32,39], others did not find such an association [10]. The assumption that more met needs would be associated with higher quality of life was not confirmed.…”
mentioning
confidence: 97%
“…Consumers with more service contacts (Lasalvia et al 2000) or who receive assertive case management (Gallagher and Teesson 2000) generally report a higher total numbers of needs. Finally, several studies have found a strong association between the number of unmet needs and poor quality of life (BengtssonTopps and Hansson 1999;Hansson et al 2003;Slade et al 2004;Van Busschbach and Wiersma 2002;Wiersma and van Busschbach 2001).…”
Section: Introductionmentioning
confidence: 96%
“…This hypothesis has been investigated in rather few, mainly cross-sectional studies, showing an robust association between more unmet needs and a worse subjective quality of life (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%